2022
DOI: 10.3389/fneur.2022.871947
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Plasma Biomarkers of Alzheimer's in a Diverse Community-Based Cohort: A Cross-Sectional Study of the HAB-HD Cohort

Abstract: BackgroundDue to their low cost, less invasive nature, and ready availability, plasma biomarkers of Alzheimer's disease have been proposed as one-time screening tools for clinical trials and research. The impact of ethnoracial factors on these biomarkers has received little attention. The current cross-sectional study investigated the levels of Aβ40, Aβ42, total tau (t tau), and neurofilament light (NfL) across diagnoses for each of the three major ethnoracial groups in the United States in a community-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…In biomarker studies of more diverse individuals, the utility of pTau-181 has been shown in predicting AD status in Caribbean Hispanics[39] as well as African Americans. [38,55] However, the larger sample sizes of diverse cohorts reported here, 3-5 times larger than previous, indicate that this is a robust and reproducible observation; that pTau-181 can be incorporated in more diverse populations as a potential aide in diagnostic prediction. However, it is clear that this biomarker lacks complete discrimination of status as there is significant overlap in individual values between AD, MCI, and CU.…”
Section: Discussionmentioning
confidence: 45%
“…In biomarker studies of more diverse individuals, the utility of pTau-181 has been shown in predicting AD status in Caribbean Hispanics[39] as well as African Americans. [38,55] However, the larger sample sizes of diverse cohorts reported here, 3-5 times larger than previous, indicate that this is a robust and reproducible observation; that pTau-181 can be incorporated in more diverse populations as a potential aide in diagnostic prediction. However, it is clear that this biomarker lacks complete discrimination of status as there is significant overlap in individual values between AD, MCI, and CU.…”
Section: Discussionmentioning
confidence: 45%
“…Also, participants of this community‐based cohort were predominantly white. Prior studies examining performance of BBBs in racial and ethnic diverse groups have been conflicting 31 , 32 , 33 , 34 and more data are needed to determine if the diagnostic performance observed in this study is applicable to more diverse populations. Finally, we used amyloid‐PET as the outcome measure; therefore, studies examining performance of BBBs using CSF biomarkers to characterize amyloid pathology may not be directly comparable as CSF markers can also have varying performance for detecting an abnormal amyloid‐PET.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, recent findings from another cohort of non‐Hispanic Whites and Black Americans suggest that while plasma Aβ42/40 consistently predicted CSF Aβ42/40 across self‐identified racialized groups, other plasma biomarkers, including phosphorylated tau (p‐tau)181, p‐tau231, and neurofibrillary tangle levels were not as consistently aligned 2 . Moreover, recent evidence suggesting differences in plasma Aβ42/40 levels between racialized groups carrying the same neurocognitive diagnoses (e.g., MCI and dementia) underscores the importance of this ongoing work 3 . In total, expansion of biomarker research in Black American cohorts 44 represents an essential next step to ensure that biomarkers accurately and consistently predict AD pathology across diverse populations.…”
Section: Discussionmentioning
confidence: 99%